The "DIARII" Program To Improve Patient Independence In The Management Of Hypertension In Banjarmasin In 2022 - Er Unja , Ermeisi; Chrismilasari, Lucia Andi; Rachman, Aulia (Jurnal EduHealth, 2022)
According to Banjarmasin City Health Office data, hypertension is still ranked among the top 10 non-communicable diseases. The increase in hypertension can be associated with unhealthy lifestyle changes. One way to make it easier for patients to control themselves, especially blood pressure control and adherence to self-management, is through health promotion programs. Therefore, researchers are interested in conducting heat promotion efforts with the "DIARII" program for the prevention and control of hypertension patients in Banjarmasin. The purpose of this study was to determine the effect of implementing the "DIARII" program in increasing the ability of patients and families to control hypertension independently. The research design used in this study was Quasi-Experimental Design with a Control Group Pre-Post Test Design. The population and samples used were 60 people with hypertension aged 26-65 in Banjarmasin. The research was conducted in several places in the city of Banjarmasin. This research has been deemed ethical by the Research Ethics Commission of the University of Muhammadiyah Banjarmasin, with the number 283/UMB/KE/IX/2022. The results showed that the value of the Wilcoxon test for family independence in the intervention group showed the importance of Sig. p Value 0.317 > 0.05 means no significant difference after the intervention. So it can be concluded that implementing the DIARII program affects the patient's ability to manage hypertension. Health promotion education interventions were found to improve the quality of life and the ability of sufferers to understand any health information they received.